The role of adaptive strategies in plant naturalization - Guo, Wen-Yong; van Kleunen, Mark; Winter, Marten; Weigelt, Patrick; Stein, Anke; Pierce, Simon; Pergl, Jan; Moser, Dietmar; Maurel, Noëlie; Lenzner, Bernd; Kreft, Holger; Essl, Franz; et al. (Ecology letters, 2018)
Determining the factors associated with the naturalization of alien species is a central theme in ecology. Here, we tested the usefulness of a metric for quantifying Grime's seminal concept of adaptive strategies - competitors, stress-tolerators and ruderals (CSR) - to explain plant naturalizations worldwide. Using a global dataset of 3004 vascular plant species, and accounting for phylogenetic relatedness and species' native biomes, we assessed the associations between calculated C-, S- and R-scores and naturalization success for species exhibiting different life forms. Across different plant life forms, C-scores were positively and S-scores negatively associated with both the probability of naturalization and the number of regions where the species has naturalized. R-scores had positive effects on the probability of naturalization. These effects of the scores were, however, weak to absent for tree species. Our findings demonstrate the utility of CSR-score calculation to broadly represent, and potentially explain, the naturalization success of plant species.
Keywords: rostliny; naturalization extent; naturalization success; functional groups; plant functional types; ekosystém; Alien species; Ecosystem; fylogeneze; Ecology; Phylogeny; life form; ekologie; Plants; Grime's CSR theory; universal adaptive strategy theory (UAST)